Cardiovascular risk in chronic autoimmune thyroiditis and subclinical hypothyroidism patients. A cluster analysis. (1st March 2017) - Carbotta, Giovanni; Tartaglia, Francesco; Giuliani, Alessandro; Carbotta, Sabino; Tromba, Luciana; Jacomelli, Ilaria; De Anna, Livia; Fumarola, Angela
Abstract: Background: Subclinical hypothyroidism (SCH) and chronic autoimmune thyroiditis (CAT) are linked to an increased risk of atherosclerosis and coronary heart disease (CHD). The aim of this study was to look for positive markers of CHD and correlations with thyroid blood tests in patients with SCH or CAT, but no symptoms of CHD, so as to identify CHD risk conditions that otherwise would likely be missed. Methods: We measured a series of thyroid, clinical-metabolic and cardiovascular parameters in 30 consecutive endocrinology patients enrolled in our ambulatory endocrinological referral center of "Sapienza" University of Rome. (19 with CAT, 11 with SCH) from January 2015 to March 2015. 13 asymptomatic subjects were enrolled as controls. In each patient, we measured a series of 34 thyroid, clinical-metabolic and cardiovascular parameters. Results: in the statistical analysis of collected data, the oblique principal components clustering procedure (OPC) revealed the presence of an interesting mixed cluster, composed of a thyroid parameter (TPO-Ab), a metabolic parameter (homocysteine level) and a cardiovascular parameter (MAPSE), in which we assessed the relationships between the single components. Our preliminary results indicate that in both groups of patients elevated TPO-Ab, when accompanied by reduced MAPSE and increased IMT and homocysteine values, may be taken to indicate the presence of clinically unrecognized CHD. Conclusions: Confirmation of these results in larger series of patients could justify hormone therapy for prevention of CHD in these thyroid patients versus placebo treatment.